PEMBERDAYAAN IBU RUMAH TANGGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN UNTUK MENINGKATKAN KAPASITAS INDUSTRI RUMAH TANGGA DI DESA WAY WAKAK, KECAMATAN ABUNG BARAT, LAMPUNG UTARA - usman raidar; Junaidi Junaidi; Erna Rochana; muhammad Guntur Purboyo (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2022)
The mandate of the 1945 Constitution article 34 paragraph 1 explains that the poor and neglected children are looked after by the State. This mandate is the legal basis for requiring the State to provide assistance to the community. Families who are part of society are mandatory and must receive benefits from the State's obligation to provide assistance. So far, direct assistance provided by the government to the community or poor families in the community is in the form of cash assistance in the form of the Program Keluarga Harapan (PKH). However, the assistance is not significant in giving impact to the community to be able to become independent families. Departing from this, it is necessary to have a formalization that has a significant impact on improving the standard of living of the community to become an independent society, namely through empowerment of housewives of PKH beneficiary families.